An Empirical Analysis of Employee Responses to Bonuses and Penalties - Van der Stede, Wim A.; Wu, Anne; Wu, Steve Yu-Ching (The Accounting Review, 2020)
ABSTRACT We examine how employees respond to bonuses and penalties using a proprietary dataset from an electronic chip manufacturer in China. First, we examine the relative effects of bonuses and penalties and observe a stronger effect on subsequent effort and performance for penalties than for bonuses. Second, we find that the marginal sensitivity of penalties diminishes faster than that of bonuses, indicating that the marginal effect of a bonus may eventually exceed that of a penalty as their value increases. Third, we find an undesirable selection effect of penalties: penalties increase employee turnover, especially for skillful and high-quality workers. These results may help inform our understanding of the observed limited use of penalties in practice due to their bounded effectiveness and possible unintended consequences. Data Availability: The confidentiality agreement with the company that provided data for this study precludes the dissemination of detailed data without the company's consent.